Indigenous peoples, poverty, and development - Hall, Gillette, 1962-; Patrinos, Harry Anthony (Cambridge : Cambridge University Press, 2012)
This book documents poverty systematically for the world's indigenous peoples in developing regions in Asia, Africa and Latin America. The volume compiles results for roughly 85 percent of the world's indigenous peoples. It draws on nationally representative data to compare trends in countries' poverty rates and other social indicators with those for indigenous sub-populations and provides comparable data for a wide range of countries all over the world. It estimates global poverty numbers and analyzes other important development indicators, such as schooling, health and social protection. Provocatively, the results show a marked difference in results across regions, with rapid poverty reduction among indigenous (and non-indigenous) populations in Asia contrasting with relative stagnation - and in some cases falling back - in Latin America and Africa.
Introduction / Gillette H. Hall and Harry Anthony Patrinos -- Indigenous peoples and development goals : a global snapshot / Kevin Alan David Macdonald -- Becoming indigenous : identity and heterogeneity in a global movement / Jerome M. Levi and Biorn Maybury-Lewis -- Indigenous peoples in Central Africa : the case of the Pygmies / Quentin Wodon, Prospere Backiny-Yetna, and Arbi Ben-Achour -- China : a case study in rapid poverty reduction / Emily Hannum and Meiyan Wang -- India : the scheduled tribes / Maitreyi Bordia Das [and others] -- Laos : ethnolinguistic diversity and disadvantage / Elizabeth M. King and Dominique van de Walle -- Vietnam : a widening poverty gap for ethnic minorities / Hai-Ahn Dang -- Latin America / Gillette H. Hall and Harry Anthony Patrinos -- Conclusion / Gillette H. Hall and Harry Anthony Patrinos.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Indigenous peoples -- Social conditions; Indigenous peoples -- Economic conditions; Indigenous peoples -- Government relations; Poverty -- Cross-cultural studies